Fiqih Masa Depan: Memahami Hukum Keluarga Islam melalui Perspektif Sistemik Jasser Auda - Masti yanto (al-Battar: Jurnal Pamungkas Hukum, 2024)
The main problem facing the Islamic world today is the failure in the process of democratization of politics, economic and educational systems, as well as the growing threat of religious extremists (fundamentalists), as well as efforts to foster pluralism and modern understanding of tolerance based on mutual understanding. The purpose of this study is to describe how to understand Islamic family law through the perspective of Jasser Auda. This research uses a qualitative method or library research, where in retrieving data using understanding in reading Jasser Auda's theory and identifying literature studies related to Islamic family law perpsective Jasser Auda. Islamic family law is expected to play a key role in formulating Islamic law that is responsive to social, cultural and technological changes. Within the framework of Jasser Auda's approach.